Dermal and muscle fibroblasts and skeletal myofibers survive chikungunya virus infection and harbor persistent RNA - Young, Alissa R. (PLoS Pathog, 2019)
Chikungunya virus (CHIKV) is an arthritogenic alphavirus that acutely causes fever as well as severe joint and muscle pain. Chronic musculoskeletal pain persists in a substantial fraction of patients for months to years after the initial infection, yet we still have a poor understanding of what promotes chronic disease. While replicating virus has not been detected in joint-associated tissues of patients with persistent arthritis nor in various animal models at convalescent time points, viral RNA is detected months after acute infection. To identify the cells that might contribute to pathogenesis during this chronic phase, we developed a recombinant CHIKV that expresses Cre recombinase (CHIKV-3ʹ-Cre). CHIKV-3ʹ-Cre replicated in myoblasts and fibroblasts, and it induced arthritis during the acute phase in mice. Importantly, it also induced chronic disease, including persistent viral RNA and chronic myositis and synovitis similar to wild-type virus. CHIKV-3ʹ-Cre infection of tdTomato reporter mice resulted in a population of tdTomato(+) cells that persisted for at least 112 days. Immunofluorescence and flow cytometric profiling revealed that these tdTomato(+) cells predominantly were myofibers and dermal and muscle fibroblasts. Treatment with an antibody against Mxra8, a recently defined host receptor for CHIKV, reduced the number of tdTomato(+) cells in the chronic phase and diminished the levels of chronic viral RNA, implicating these tdTomato(+) cells as the reservoir of chronic viral RNA. Finally, isolation and flow cytometry-based sorting of the tdTomato(+) fibroblasts from the skin and ankle and analysis for viral RNA revealed that the tdTomato(+) cells harbor most of the persistent CHIKV RNA at chronic time points. Therefore, this CHIKV-3ʹ-Cre and tdTomato reporter mouse system identifies the cells that survive CHIKV infection in vivo and are enriched for persistent CHIKV RNA. This model represents a useful tool for studying CHIKV pathogenesis in the acute and chronic stages of disease.